Internalization of Islamic Religious Values Based on Muhasabah To Increase Students' Spiritual Intelligence (Arfannur: Journal of Islamic Education, 2024)
This study reveals that attention to the practical aspects of religion in the process of Islamic Religious Education (PAI) has not been maximized, because it focuses more on achieving cognitive aspects. This study aims to determine: 1) The program of religious attitude habituation method based on muhasabah at SMAN 2 Cikarang Utara, 2) The condition of students' spiritual intelligence during school activities, and 3) Supporting and inhibiting factors of muhasabah activities. The study used a qualitative approach with case study and descriptive analytical methods. Data were collected through observation, interviews, and documentation. The results showed that the muhasabah method involved praying together, praying Duha, reciting the Qur'an, lectures, and social activities to form a religious character quite significantly. Students' spiritual intelligence generally increased well, in aspects of worship, and social attitudes, which were influenced by family support and personal motivation, but there were still obstacles, namely lack of family communication, negative environmental influences, and minimal understanding of religion. Supporting factors include school leadership, teaching quality, positive environment. Inhibiting factors include lack of motivation, family support, and negative environmental influences. The research recommendation is that collaboration is needed between schools, families and communities to overcome these obstacles so that students' spiritual intelligence continues to increase.